Improving quality of teaching method in history and theory of architectural education via technology enhanced active learning method - Tidjani, Abhari Ahmat (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2020)
The growing concern about History and Theory of Architectural (HTA) education has been an area of substantial research interest. The central aim of this research is to examine the relevance of Mobile Augmented Reality (MAR) and its potential benefit in teaching and learning History and Theory of Architecture (HTA) in design schools. The objectives of the research are; to identify the current educational technology used in HTA education, to investigate the role of MAR application in HTA education and to evaluate MAR technology's effectiveness in generating favourable learning outcomes. The scope of the investigation focuses on two higher learning institutions; International Islamic University Malaysia (IIUM) and University Sains Islam Malaysia (USIM). The research is built on threefold dimensions of the research questions, objectives and sources of the relevant data. Regarding the approach, a mixed-method was used in generating relevant information to the investigation ranging from an in-depth interview, observation and survey questionnaires. About the techniques, content analysis, reflective remarks and descriptive analysis are applied in data interpretation. Based on the findings, the major setback of HTA lies in the methodological lapses in the dominant teaching method. In addressing this issue, the study proposes a useful notion on how to improve the quality of the current teaching method by adopting MAR technology in the teaching strategy. The effectiveness of this application was evident from the conducted workshop where a factual assessment was made based on the learning feedback from the students.